The role of Waqf and Trust Commission (WTC) in Zanzibar: problems and prospects - Moh’d, Issa Salim; Mohammad, Mustafa Omar; Saiti, Buerhan (Islami Bank Training and Research Academy (IBTRA), 2017)
Waqf as institution has played a great role in the past. Several examples are cited to show the socio-economic contributions this institution had played in the past especially in the Muslim communities. This institution offered many notable public services that are today financed by the state or the government, such as education, health care, national security, transportation facilities, the basic infrastructure, food, shelter and jobs. Generally, waqf institutions of Muslim countries like Madina, Turkey (during Othman Empire), Algeria (under French occupation), Egypt, Palestine, Jerusalem, Iraq and Tunisia had a remarkable contribution. Meanwhile, this role did not exempt Zanzibar since 1800s. The significant contribution by the waqf in Zanzibar is considerable as well. However, this institution in the Islands has been facing several problems and as well as the problem of funding the waqf and Trust Commission. This paper, therefore, examines the problems of waqf Institutions and proposes some suggestions to how to address them.